Short duplication within the RHCE gene associated with an in cis deleted RHD causing a Rhnull amorph phenotype in an immunized pregnant woman with anti‐Rh29. Issue 6 (21st November 2014) - Silvy, Monique; Beley, Sophie; Peyrard, Thierry; Ouchari, Mouna; Abdelkefi, Saadia; Jemni Yacoub, Saloua; Chiaroni, Jacques; Bailly, Pascal
Abstract : Background: The rare amorph Rhnull phenotype is caused by silent alleles at the RH locus and usually arises in consanguineous families. To date, only five molecular backgrounds have been identified in five unrelated families. Subjects with Rhnull red blood cells (RBCs) readily produce alloantibodies to high‐prevalence Rh antigens. Study Design and Methods: RBCs from a pregnant woman (G5P3) from Libya, with a positive indirect antiglobulin test were phenotyped by hemagglutination. RHD and RHCE genes were analyzed at the genomic level and mutation inheritance pattern was assessed in the patient's family. Results: Hemagglutination testing showed a D–C–E–c–e– phenotype in the proposita associated with the presence of a high titer anti‐Rh29 (4096). Molecular analysis revealed a deletion of RHD and presence of a novel RHCE allele with a 7‐bp duplication in Exon 7. This duplication is predicted to introduce a frameshift after His350, a new C‐terminal sequence, and a premature stop codon resulting in shortened predicted protein with only 402 amino acids. The mutated allele was found at homozygous state in the proposita and heterozygous state in her parents and one brother. Conclusion: This report describes a novel RHCE mutation causing the loss of RhCE antigen expression in association with RHD deletion, leading to an amorph Rhnull phenotype.